High-performance aqueous rechargeable nickel//bismuth batteries with Bi2MoO6@rGO and Co0.5Ni0.5MoO4@rGO as electrode materials. (7th February 2023) - Kang, Wei-Wei; Zhao, Ya-Nan; Zhang, Wen-Qing; Sun, Ying; Zhang, Xue-Qin; Yi, Gui-Yun; Huang, Guang-Xu; Xing, Bao-Lin; Zhang, Chuan-Xiang; Lin, Bao-Ping
Abstract : Aqueous rechargeable nickel–bismuth batteries have surfaced as a prospective energy storage and conversion system because of their merits of good safety, high power density, and low cost. Abstract : Aqueous rechargeable nickel//bismuth batteries have surfaced as a prospective energy storage and conversion system because of their merits of good safety, high power density, and low cost. Their electrochemical performances, however, are heavily dependent on the electrode active materials. Herein, high-performance aqueous rechargeable nickel//bismuth batteries were assembled with Bi2 MoO6 @reduced graphene oxide (rGO) as the anode active material and Co0.5 Ni0.5 MoO4 @rGO as the cathode active material. Introducing rGO could effectively enhance the utilization of the electrode active materials, improving the specific capacity and rate performance. The Bi2 MoO6 @rGO delivered a specific capacity of 198.0 mA h g −1 at the current density of 1 A g −1 and rate property of 75.9% in 1–20 A g −1 . Additionally, the Co0.5 Ni0.5 MoO4 @rGO exhibited specific capacities of 150.5 and 110.8 mA h g −1 at 1 and 15 A g −1, respectively. Accordingly, the nickel//bismuth batteries afforded a maximum energy density of 53.1 W h kg −1 with a power density of 351.6 W kg −1 at 0.5 A g −1 . This research demonstrates the great prospects for aqueous nickel//bismuth batteries and enriches the field of battery electrochemical systems.